The peculiarities of individual productivity formation of soybean plants (Glycine hispida Moench.) under conditions of different supply with elements of mineral nutrition - Yeremko, L.; Hanhur, V. (Scientific Progress & Innovations, 2022)
Soybean is a strategic crop of global importance that plays a key role in overcoming the food crisis. Its grain has a unique combination of organic compounds and mineral substances of the two most important components - protein and oil, which play a key role in the physiological and biochemical processes of human and animal life. Formation of crop productivity occurs during the growing season in close relationship with life factors. In their group, one of the key positions is occupied by the nutrient regime of the soil. The use of the microbiological preparations, macro - and microfertilizers are important agrotechnical methods that able to improve the supply of plants with elements of mineral nutrition. The purpose of the research is to find out the effect of mineral fertilizers, microelements and a microbiological preparation based on the nitrogen -fixing microorganisms on the soybean productivity formation. Results of the research indicate that the presowing seed treatment with the microfertilizer and microbiological preparation contributed to intensification of growth processes, formation of the optimal optical and biological structure of crops and the corresponding improvement of the conditions of development and formation of plants biological productivity in them. The combination of such agrotechnical methods proved to be the most effective in the variant with application of mineral fertilizers in a dose of active substance N 35P70K70. In this case, an average of 18.2 pcs. beans were formed on the plants, with an average number of grains in them of 2.3 pcs. The total number of grains from a plant and the weight of 1000 of them were, respectively, 41.9 pcs. and 157.4 g. The size of the structural elements of individual plant productivity and their number per unit area determined the level of crop productivity. Accordingly, its values were the highest in general according to the experiment (2.78 t ha-1) in the variants with a combine using of mineral fertilizers with a dose of active substance N35P70K70, a microbiological preparation and microfertilizer. In the variant where the pre-sowing seed treatment was carried out only with a microbiological preparation, a decrease in the grain productivity of soybean crops was noted, compared to the complex application of macro- and microfertilizer and a microbiological preparation, by 0.1–0.12 t ha-1.